Engineering performance and environmental assessment of sustainable concrete incorporating nano silica and metakaolin as cementitious materials - Namitha Raveendran; Vasugi Krishnan (Scientific Reports)
Abstract The carbon footprint associated with cement production, coupled with depletion of natural resources and climate change, underscores the need for sustainable alternatives. This study explores the effect of metakaolin (MK) and nano-silica (NS) on concrete’s engineering performance and environmental impact. Initially, compressive, tensile, and flexural strength tests, along with durability assessments like water absorption, sorptivity, rapid chloride permeability, and resistance to acid and sulphate attacks, were conducted. Later, X-ray Diffraction spectroscopy and Field-emission scanning electron microscopy were employed for microstructural analysis. Subsequently, the environmental impact of micro and nano materials was assessed using embodied carbon emissions and eco-strength efficiency. The results revealed that the hybrid mixes of 12.50% MK and 2% NS (M7) showed superior performance, demonstrating significant strength enhancements and eco-efficiency, achieving 0.15 MPa/kg CO2/m3 at 28th day. Meanwhile, the MK-only mix (M6) yielded the lowest embodied CO2 emissions at 330 kg CO2/m3. MK and NS effectively reduce porosity and enhance durability against environmental factors while lowering clinker content, contributing to sustainability. Furthermore, the microstructural behaviour showed early hydration, dense microstructure and additional Calcium Silicate Hydrate formation, leading to improved properties. The outcomes reveal that the concrete configuration has altered at micro and nano levels by the inclusion of MK and NS, demonstrating their substantial contribution to producing environmentally friendly, effective, and beneficial concrete.